EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN APEL DI DESA SIHIONGKECAMATAN BONATUA LUNASI KABUPATEN TOBA SAMOSIR - Carlos Samuel; Bintang Sitorus; Supriadi Supriadi (Jurnal Agroekoteknologi, 2013)
The objective of this research is to evaluate the land  suitability for Apple Trees at Sihiong Village,Bonatua Lunasi Subdistrict, Toba Samosir District. The results of this study showed that 11 soilmap units found based on the map of soil and the map of topography, and than it makes to overlay.The evaluation of land suitability  classes based on the criteria given by Resesarch Center,IPBBogor  1983 and the evaluation method  is limitation method based on FAO 1976. The results ofthis research showed that  the highest actual of land suitability classes is land mapping unit two (S3nr,eh) and the highest potential of land suitability classes is land mapping unit 1,3,5,7,8,10,11 (S1)Keywords: land suitability evaluation,apples, sihiong village